2020
DOI: 10.1101/2020.08.04.235994
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic analysis of obstructive sleep apnoea discovers a strong association with cardiometabolic health

Abstract: There is currently only limited understanding of the genetic aetiology of obstructive sleep apnoea (OSA). The aim of our study is to identify genetic loci associated with OSA risk and to test if OSA and its comorbidities share a common genetic background. We conducted the first large-scale genome-wide association study of OSA using FinnGen Study (217,955 individuals) with 16,761 OSA patients identified using nationwide health registries. We estimated 8.3% [0.06-0.11] heritability and identified five loci asso… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 45 publications
2
44
0
Order By: Relevance
“…As a proof-of-principle of the utility of having well-powered GWAS summary statistics, we performed a hypothesis-free inference of causal associations between >400 traits and our sleep apnoea MTAG. Consistent with previous findings 45 , our approach inferred obesity to likely increase the risk for sleep apnoea. Similar results were found for asthma, lung cancer, hernia, hypertension, ever having a period of mania and stroke.…”
Section: Discussionsupporting
confidence: 87%
“…As a proof-of-principle of the utility of having well-powered GWAS summary statistics, we performed a hypothesis-free inference of causal associations between >400 traits and our sleep apnoea MTAG. Consistent with previous findings 45 , our approach inferred obesity to likely increase the risk for sleep apnoea. Similar results were found for asthma, lung cancer, hernia, hypertension, ever having a period of mania and stroke.…”
Section: Discussionsupporting
confidence: 87%
“…Of all patients with COVID-19 diagnosis (N=305, 38% male, mean age 55.2 years) 26 patients also had OSA diagnosis (8.5%, 46.2% male, mean age 63.0), (Table 1, Table 2). This reflects a similar prevalence of OSA diagnoses in COVID-19 infected as in the normal population in FinnGen, where prevalence is 8% 15 . 83 patients required hospitalization (38.6% male, mean age 66.3 years) including 16 OSA patients.…”
Section: Resultssupporting
confidence: 67%
“…Third, we attempted to examine the relationship between sleep apnoea and depression in a population using MR. However, studies have reported sleep apnoea heritability estimates of 8.3% (0.06-0.11), whereas there are only five SNPs associated with sleep apnoea (P < 5.0 × 10 −8 ), including three SNPs in UK Biobank [44].…”
Section: Discussionmentioning
confidence: 99%